The phenomenal self - Dainton, Barry, 1958- (Oxford : Oxford University Press, 2008)
Barry Dainton presents an account of the self, grounded in the continuity we find in our streams of consciousness: this is the key to explaining how we can undergo changes but remain the same person.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Self (Philosophy); Phenomenalism; Phenomenology; Self